2021
DOI: 10.3389/fmed.2020.615599
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Markers, Soluble CD163 and Mannose Receptor, in Liver Fibrosis

Abstract: Macrophages are essential components of the human host immune system, which upon activation facilitates a broad pallet of immunomodulatory events including release of pro- or anti-inflammatory cytokines and chemokines, restoration of immune homeostasis and/or wound healing. Moreover, some macrophage phenotypes are crucially involved in fibrogenesis through stimulation of myofibroblasts, while others promote fibrolysis. During the last decades, the role of resident liver macrophages viz. Kupffer cells and recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…In order to affirm the hypothesis that Greenlanders are less likely to develop liver fibrosis than Danes, future studies will benefit from a longitudinal design and require patient cohorts with a larger control group, a larger proportion suffering from moderate and advanced liver fibrosis, and inclusion of Fibroscan® or biopsy specimens for comparison. Also, other promising non-invasive biomarkers of liver steatosis and fibrosis may be relevant to evaluate in Arctic populations in future studies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to affirm the hypothesis that Greenlanders are less likely to develop liver fibrosis than Danes, future studies will benefit from a longitudinal design and require patient cohorts with a larger control group, a larger proportion suffering from moderate and advanced liver fibrosis, and inclusion of Fibroscan® or biopsy specimens for comparison. Also, other promising non-invasive biomarkers of liver steatosis and fibrosis may be relevant to evaluate in Arctic populations in future studies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The M-type phospholipase A 2 receptor has a high degree of homology (~30%) to mannose receptors, a member of the lectin receptor family, constitutively expressed in macrophages [38,39]. Mannose receptors are involved in phagocytosis, antigen processing [29,38,40], and the production of inflammatory cytokines by macrophages [40][41][42]. Additionally, this receptor has been demonstrated to play a role in cell proliferation and AA release, via MAPKs (protein kinase activated by the mitogens family), induced by the group IB sPLA 2 s [43][44][45].…”
Section: Phospholipases Amentioning
confidence: 99%
“…Although its physiological role remains unknown, sCD163 is recognized as a strong marker for macrophage activation. 13 Several clinical studies have indeed reported that blood sCD163 levels are increased in patients with acute inflammatory diseases such as sepsis and acute hepatitis. 1,4 In addition, high serum sCD163 levels could be associated with the severity of chronic fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 In addition, high serum sCD163 levels could be associated with the severity of chronic fibrotic diseases. Increased serum CD163 concentrations constitute a relevant biological marker for aggravation of HBV and HCV-related liver fibrosis 3,5 and interstitial lung disease (ILD) associated with inflammatory myositis. 6 Idiopathic pulmonary fibrosis (IPF) is an irreversible and rapidly fatal diffuse ILD.…”
Section: Introductionmentioning
confidence: 99%